APPLICATION OF THE TEAM ASSISTED INDIVIDUALIZATION MODEL OF LEARNING IN INCREASING HIGH SCHOOL STUDENTS' LEARNING MOTIVATION - Suryani, Suryani; Putri, Desy Hanisa; Risdianto, Eko (Universitas Tanjungpura, 2024)
This research was conducted to determine the increase in learning motivation and student responses to the application of the Team Assisted Individualisation learning model on elasticity material. This type of research is a pre-experiment research with One-group pretest-posttest design. The research sample was taken with random sampling technique. The results of the data analysis of the learning motivation questionnaire after the application of the TAI learning model resulted in a very high category and an N-gain value of 0.45 which is in the medium category. This is evidenced by the results of the data analysis test using the t-test: Two-Sample Assuming Equal Variances with Î± = 0.05 assisted by Ms.Excel produces good results (P (T =t)) 0.000 for one-tail and two-tail less than the value of Î± = 0.05. Based on the results of data analysis of student response questionnaires showed a percentage score of 87% in the very high category.